BEBERAPA ASPEK ABORSI - Masri Singarimbun (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1994)
Abortion is prohibited by the law in Indonesia and it is permitted only on narrow medical grounds, i.e. to save the life of the pregnant woman. The Moslem religious leaders hold the same view.The incidence of illegal abortion is unknown. However, research findings in hospitals show that induced abortion is increasing. Contraceptive failure is one of the important factors for married women which is associated to the motivation to have a relatively small family. Another factor is the changing sexual behaviour of unmarried women. People are much mobile nowadays and are experiencing more sexual stimulations through the mass media, films, and various entertainments.In order to prevent abortion among the unmarried there is thus a growing need for family planning information and services. It is, however, a very sensitive issue, and is unlikely that the government or the non government organizations would provide such services. Even those who experience contraceptive failures in the government family planning program have, in general, no access to save abortion.